Serum electrolyte and calcium abnormalities in neonates with birth asphyxia - GNANAVELU, I.; KHER, ANJALI (International Journal of Psychosocial Rehabilitation, 2020)
Background: Birth asphyxia is defined as cessation of breathing or gasping type of breathing with Apgar score of less than 7 at 1 minute of age, with umbilical cord blood ph less than 7. Birth asphyxia is one of the leading cause of neonatal mortality in India and accounts for 23% of all neonatal deaths(1). Hypoxic- ischemic encephalopathy (HIE) is a term that describes clinical evidence of encephalopathy with objective data to support a hypoxic-ischemic (HI) mechanism as the underlying cause for the encephalopathy. Objectives: To compare serum electrolyte and calcium levels at less than 12 hrs with levels at 24 – 48 hrs. and it’s correlation with immediate short term outcome of neonates with birth asphyxia, severity of birth asphyxia and HIE staging. Methodology: Serum sodium, potassium and calcium estimation will be done at birth to 12 hours of birth and repeated at 24 to 48 hours of birth in full term neonates diagnosed with birth asphyxia. Sample will be collected by pricking a peripheral vein or when securing i.v.canula. Results: would be undertaken with SPSS. Conclusion: would be Based on findings of the study.